A REVIEW ON THE IMPACT OF AI ON VARIOUS INDUSTRIES - Jha, Amit; Sen, Gaurav; Kulshrestha, Geeta; Tulsi, Piyush (International Journal of Psychosocial Rehabilitation, 2020)
Artificial intelligence is one of the most used words in this world these days. It refers to a manmade software used for intelligence. It has a capability to think like a human and it give a spontaneous reaction to every question that we asked. It has a large amount of information that a human cannot have it in their brain. From last decade ai has developed a lot. Ai is very useful in many of the fields. Many industries are using ai for promoting their product and to manage things like accounts, technology, sales, etc. Even ai can detect problems if any. Many researchers have explained the pros and cons of ai in various field. The major con of ai is that it can give wrong information sometimes. It has replaced many employees now a days. Artificial intelligence offers self assists to human beings. It is helpful in all the fields.